(untitled) (Al-Qamar, 2022)
Muslim society has distinct communal norms from the West. The modernization of the global world created tension for Muslim zones, particularly Muslim Family Laws. Classical Islamic family law permitted the husband to enter into a maximum of four marriages at a time. In the contemporary Muslim world, Polygamy has marked the most contentious and unsettled legal issue. It requires an academic study on the advantages and disadvantages of Polygamy. The state of Pakistan introduced some impediments and edits for a second marriage to secure women’s rights Failure to the state regulations will impose criminal liability on the husband. The paper in hand will analyze the confinements of the state in MFLO (Muslim Family Laws Ordinance), 1961. It will depict the contraventions of this enactment from Islamic law. This paper will examine the views of judicial and constitutional institutions on polygamous provisions.